2019
DOI: 10.3390/nu11112719
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Antioxidants and Sensory Properties of Italian Chocolates and Related Ingredients Under Controlled Conditions During an Eighteen-Month Storage Period

Abstract: Background: While there has been an increasing interest in the health properties of chocolate, limited research has looked into the changes of antioxidants occurring in the time span from production to the best before date, which was a period of 18 months in this study. Methods: Humidity, ash, pH, acidity, fiber, carotenoids, retinols, tocopherols, sugars, proteins, theobromine, caffeine, polyphenols, fats, the peroxide value, organic acids, and volatile compounds, along with the sensory profile, were monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
2
5
1
Order By: Relevance
“…It ranged from 0.73 mg GAE/g of defatted sample to 1.52 mg GAE/g of defatted sample for milk chocolates, and from 2.41 mg GAE/g of defatted sample to 3.61 mg GAE/g of defatted sample for dark chocolates, as determined by modified Folin-Ciocalteau method. The addition of cocoa shell reduced TPC, with more pronounced effect as cocoa shell content increased from 5% to 15% in dark chocolate; however, TPC in all analyzed samples was larger than reported by Roda and Lambri [ 13 ] for dark (2.12 mg GAE/g of defatted sample) and milk (0.64 mg GAE/g of defatted sample) chocolate. Belščak-Cvitanović et al [ 14 ] reported TPC content of approximately 3.5–5.5 mg GAE/g of defatted sample for milk chocolate and approximately 7.5–12 mg GAE/g of defatted sample for dark chocolate.…”
Section: Resultscontrasting
confidence: 60%
“…It ranged from 0.73 mg GAE/g of defatted sample to 1.52 mg GAE/g of defatted sample for milk chocolates, and from 2.41 mg GAE/g of defatted sample to 3.61 mg GAE/g of defatted sample for dark chocolates, as determined by modified Folin-Ciocalteau method. The addition of cocoa shell reduced TPC, with more pronounced effect as cocoa shell content increased from 5% to 15% in dark chocolate; however, TPC in all analyzed samples was larger than reported by Roda and Lambri [ 13 ] for dark (2.12 mg GAE/g of defatted sample) and milk (0.64 mg GAE/g of defatted sample) chocolate. Belščak-Cvitanović et al [ 14 ] reported TPC content of approximately 3.5–5.5 mg GAE/g of defatted sample for milk chocolate and approximately 7.5–12 mg GAE/g of defatted sample for dark chocolate.…”
Section: Resultscontrasting
confidence: 60%
“…The same tendency was reported by Fernández et al. (2011) [ 55 ]. Furthermore, these TPC values are higher than in fruits such as grapes, acai, guava, strawberry, pineapples, soursop and passionfruit [ 63 ].…”
Section: Resultssupporting
confidence: 90%
“…Examining at the industrialization process, it can be observed that one of the key steps is obtaining the roasted grains, where the TPC drops below 100 mg GAE/g [ 39 , 40 ]. After obtaining one of the main subproducts available in the market (i.e., cocoa liquor), polyphenol values are well below 50 mg GAE/g [ 77 ]; while cocoa powder shows values under 15 mg GAE/g [ 53 , 78 ]. Finally, the range of polyphenol content in chocolate preparations is wide due to the different available preparations of this cocoa derivative.…”
Section: Resultsmentioning
confidence: 99%
“…A small loss of antioxidant activity by 2.5% on average was also observed in all samples after 8 months of storage, as seen by DPPH inhibition values that decreased to 11.1-11.6% levels. This finding is in accordance with other similar studies regarding the effect of storage on the antioxidant capacity of chocolate products (Pavlovic et al, 2017) and is related to the degradation of major polyphenol compounds (flaval-3-ols, anthocyanins, catechins, procyanidins and proanthocyanidins) (Laličić-Petronijević et al, 2016;Pavlovic et al, 2017;Roda and Lambri, 2019).…”
Section: Antioxidant Activity and Color Properties Of Chocolate Products During Storagesupporting
confidence: 93%